2012
DOI: 10.1152/ajpregu.00591.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of an antisense RNA with the transition of neonatal to IIb myosin heavy chain during postnatal development and hypothyroidism in rat skeletal muscle

Abstract: Regulation of an antisense RNA with the transition of neonatal to IIb myosin heavy chain during postnatal development and hypothyroidism in rat skeletal muscle. Am J Physiol Regul Integr Comp Physiol 302: R854 -R867, 2012. First published January 18, 2012 doi:10.1152/ajpregu.00591.2011.-Postnatal development of fast skeletal muscle is characterized by a transition in expression of myosin heavy chain (MHC) isoforms, from primarily neonatal MHC at birth to primarily IIb MHC in adults, in a tightly coordinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…In addition, MYH3 coding the embryonic isoform locates 5' to MYH2 while MYH8 coding the neonatal isoform locates 3' to MYH4. According to Pandorf et al (2012), the expression of MYH4 mRNA (coding MHC 2b) increased until day 20 of the postnatal life in Plantaris muscle of the rat, whereas MYH8 mRNA (coding the neonatal isoform) disappeared in the same period. When the new born rats were given PTU in order to induce hypothyroidism, the expression of MYH4 mRNA in the Plantaris muscle remained low, while that of MYH8 mRNA was observed even on day 40 of postnatal life (Pandorf et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MYH3 coding the embryonic isoform locates 5' to MYH2 while MYH8 coding the neonatal isoform locates 3' to MYH4. According to Pandorf et al (2012), the expression of MYH4 mRNA (coding MHC 2b) increased until day 20 of the postnatal life in Plantaris muscle of the rat, whereas MYH8 mRNA (coding the neonatal isoform) disappeared in the same period. When the new born rats were given PTU in order to induce hypothyroidism, the expression of MYH4 mRNA in the Plantaris muscle remained low, while that of MYH8 mRNA was observed even on day 40 of postnatal life (Pandorf et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…According to Pandorf et al (2012), the expression of MYH4 mRNA (coding MHC 2b) increased until day 20 of the postnatal life in Plantaris muscle of the rat, whereas MYH8 mRNA (coding the neonatal isoform) disappeared in the same period. When the new born rats were given PTU in order to induce hypothyroidism, the expression of MYH4 mRNA in the Plantaris muscle remained low, while that of MYH8 mRNA was observed even on day 40 of postnatal life (Pandorf et al 2012). The results indicate that the transition from the neonatal isoform to MHC 2b, two isoforms located in the vicinity of the same chromosome, might have been delayed by the hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms controlling the myosin switch during development remain to be established and probably involve specific regulatory sequences associated with the MYH gene cluster, where MYH genes are arranged in the order: MYH3 - MYH2 - MYH1 - MYH4 - MYH8 - MYH13 . It has been reported that thyroid hormone controls the transition between neonatal and adult fast 2B MyHC by a long non-coding antisense RNA which is transcriptionally regulated during postnatal development and in response to hypothyroidism: this antisense RNA is transcribed from a site within the intergenic region between MYH8 (MyHC-neo) and the closely associated MYH4 (MyHC-2B) gene and appears to mediate the transcriptional repression of the MYH8 gene [ 40 ]. A central enhancer located between the MYH3 and MYH2 genes has been recently identified [ 41 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, postnatal changes in MyHC isoform mRNA transcription were found to be regulated by a natural antisense transcript (bII NAT) such that expression of MyHC Neo is positively correlated with expression of bII NAT whereas expression of MyHC 2B is negatively correlated. Thus, postnatally expression of bII NAT can play a critical role in coordinating the transition from MyHC Neo to adult MyHC 2B (and possibly MyHC 2X ) isoforms (315). Recently, it was shown that postnatal changes in MyHC isoform mRNA expression in the rat diaphragm muscle do not match the changes in MyHC protein expression, suggesting that changes in MyHC isoform expression in the developing rat diaphragm muscle are not driven solely by changes in mRNA expression (136).…”
Section: Respiratory Muscle Structurementioning
confidence: 99%